2023
DOI: 10.1525/collabra.68054
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Responding in Support of Donald Trump: An Extended Replication of Schaffner and Luks (2018)

Abstract: There is considerable debate about whether survey respondents regularly engage in “expressive responding” – professing to believe something that they do not sincerely believe to show support for their in-group or hostility to an out-group. Nonetheless, there is widespread agreement that one study provides compelling evidence for a consequential level of expressive responding in a particular context. In the immediate aftermath of Donald Trump’s 2017 presidential inauguration rally there was considerable controv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is possible that the current study and the studies of Ross et al (2016) and So et al (2023) failed to find clear evidence of cognitive biases because they were conducted online, where participants can be careless (Brühlmann et al, 2020) and dishonest (Ross & Levy, 2023). However, this seems unlikely because research suggests that participants in online studies are at least as diligent—or even more diligent—than participants in the laboratory (Hauser & Schwarz, 2016; Kees et al, 2017; Ramsey et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It is possible that the current study and the studies of Ross et al (2016) and So et al (2023) failed to find clear evidence of cognitive biases because they were conducted online, where participants can be careless (Brühlmann et al, 2020) and dishonest (Ross & Levy, 2023). However, this seems unlikely because research suggests that participants in online studies are at least as diligent—or even more diligent—than participants in the laboratory (Hauser & Schwarz, 2016; Kees et al, 2017; Ramsey et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…3In fact, there is compelling evidence that surprisingly large numbers of people are willing to lie about their beliefs in surveys in certain contexts (Ross & Levy, 2023). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Further, incentives to report accurately reduce the partisan gap in responses (Prior et al, 2015 ). Most compellingly Schaffner and Luks ( 2018 ) found that Republicans were significantly more likely than Democrats to report that an (unlabelled) photograph of the Trump inauguration depicted a larger crowd than a similar photograph of the Obama inauguration (see Ross & Levy, 2022 for a replication). It’s really not plausible that they truly believe that the first photo depicts a bigger crowd; rather, they’re expressing their support for one side of politics.…”
Section: Excessive Humility?mentioning
confidence: 99%